The pigmentation interference of bisphenol F and bisphenol A. (November 2020) - Mu, Xiyan; Liu, Jia; Yuan, Lilai; Huang, Ying; Qian, Le; Wang, Chengju
Abstract: Bisphenol A (BPA) and bisphenol F (BPF) are widely distributed in the environment and daily consumptions, leading to exposure toward human and environmental animals. The potential risk of bisphenol analogs on pigment and skin health is not well documented. In this study, we found that 0.05 mg/L BPF (tolerated daily intake (TDI) value of BPA) affected the particle size and color density of zebrafish melanin. While BPA caused less depigmentation effect toward zebrafish with effective concentration of 5.0 mg/L. The downregulation of melanin synthases induced by BPF is associated with the reduction in melanin. Molecular dynamics indicated that both BPF and BPA could act as ligands of zebrafish and human Tyr family proteins; however, these compounds have completely different energetics and spatial steric effects, potentially explaining their varying depigmentation effects. Additionally, an in vitro assay using A375 melanoma cells demonstrated that the inhibitory effect of BPF on human melanin production was primarily attributed to Tyr inhibition. These findings provide an important basis for understanding the molecular mechanisms of BPF and BPA in melanin inhibition, and the results reflect the skin pigmentation interference risk of these compounds, which are ubiquitous in everyday personal products. Graphical abstract: Image 1 Highlights: BPF exposure during zebrafish embryonic stage has real and measurable effects on pigmentation. BPF and BPA had varying melanin inhibitory activities on zebrafish embryos. The depigmentation effect of BPs was possibly due to the inhibition of melanin biosynthases. Both in vitro and in silico evidence demonstrating the depigmentation effect of bisphenol analogs towards human. Abstract : BPF and BPA had varying melanin inhibitory activities on zebrafish embryos.